1999
DOI: 10.1007/pl00005366
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme inhibitors block mitogenic signalling pathways in rat cardiac fibroblasts

Abstract: We studied the effects of angiotensin converting enzyme (ACE) inhibitors on angiotensin II (Ang II) induced growth related signalling pathways in neonatal rat cardiac fibroblasts. In BrdU proliferation assays, Ang II (10(-9)-10(-7) M) stimulated cardiac fibroblast growth in a dose-dependent fashion (maximum at 10(-7) M, 5.22 +/- 0.01-fold, n = 9). 2-2-(1-(ethoxycarbonyl)-3-phenylpropyl)[amino-oxopropyl]-6,7-dimethoxy- 1,2,3,4-tetrahydroisoquinoline-3 carboxylic acid (moexiprilat) led to a dose-dependent inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…35 Furthermore, ACE inhibitors may elicit pleiotropic effects independently of local ACE inhibition 36 through direct regulation of cardiac Na ϩ /K ϩ pump activity 37 or mitogen activated protein kinase signal transduction. 38 One final consideration is that the whole heart is more complex than the isolated cardiomyocyte, and the multiple cell types and messenger systems that are present simultaneously are likely to modulate responses to different antihypertrophic agents. In the present study, any influences on hypertrophic markers and accumulation of cyclic GMP were assumed to be due to direct actions rather than secondary to a vasoactive action of the drug treatments, given that coronary flow varied little with different treatments in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…35 Furthermore, ACE inhibitors may elicit pleiotropic effects independently of local ACE inhibition 36 through direct regulation of cardiac Na ϩ /K ϩ pump activity 37 or mitogen activated protein kinase signal transduction. 38 One final consideration is that the whole heart is more complex than the isolated cardiomyocyte, and the multiple cell types and messenger systems that are present simultaneously are likely to modulate responses to different antihypertrophic agents. In the present study, any influences on hypertrophic markers and accumulation of cyclic GMP were assumed to be due to direct actions rather than secondary to a vasoactive action of the drug treatments, given that coronary flow varied little with different treatments in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,[21][22][23][24] Equal loading was checked by stripping and reprobing the membrane with troponin C. The following primary antibodies were used: ACE (BMA Biomedicals AG); ANP (Phoenix Pharmaceuticals Inc); angiotensin type 1 receptor (AT 1 R), ERK1/2, JNK, MKP1, p38-MAPK, phospho-JNK (Thr183/Tyr185), and troponin C (Santa Cruz Biotechnology Inc); and phospho-ERK1/2 (Thr202/Tyr204) and phospho-p-38 MAPK (Thr180/Tyr182) (New England Biolabs GmbH). Detection was performed with the enhanced chemiluminescence technique after incubation with a suitable secondary antibody coupled to horseradish peroxidase (ECL; Amersham Pharmacia Biotech).…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…Furthermore, myocardial inflammation as evidenced by polymorphonuclear leukocyte accumulation in ischemia/reperfusion tissue is markedly attenuated by prior p38 MAPK inhibition (Gao et al, 2002). Cell-based studies have reported that neurohormonal factors AngII, endothelin-1, and phenylephrine (Clerk et al, 1998;van Eickels et al, 1999), as well as ischemia (Mackay and Mochly-Rosen, 1999), are known to increase p38 MAPK activity. Furthermore, in myocytes transfected with mitogen-activated protein kinase kinase (MKK) 6, an upstream mediator of p38 MAPK, inflammatory markers are increased in response to cytokine simulation, an effect that is attenuated by p38 MAPK inhibition (Degousee et al, 2003).…”
mentioning
confidence: 99%